Methodology For Improving The Dynamics Of Development Of Relative Indicators Of Handball Players' Types Of Training In Qualification - Yusupov Zafarjon (Zien Journals, 2025)
This article describes the methods for determining and improving the dynamics of the development of relative indicators allocated to types of training in the selection of handball players at the training and training stage, as well as the impact of these methods on the special physical training of handball players. The processes of achieving improvement in targeted indicators by training hours by determining relative indicators allocated to types of training are widely covered.
Keywords: types of training; handball players; qualifying; relative performance